Entrepreneurs: Challenges and Expectations / Normah Ahmad - Ahmad, Normah (Universiti Teknologi MARA, Perlis, 2005)
Entrepreneurs are important to the economic development of a nation. The survival, growth and development of entrepreneurs much depend on their ability to deal with the challenges and complexities of k economy. Among the challenges are their ability to spot opportunities and to develop their subsector. Technological knowledge, organisational knowledge and marketing knowledge is a need to help the entrepreneurs face the challenges. Government involvement and networking between small and large organisations also help respond to the competitive challenges and market opportunities.